Scale economies, scope economies, and structure conduct performance relationships in Jordanian banking system, 1990-2000 - Barakat, Hassan Hasan, author; Phillips, Ronnie, advisor; Johnson, Richard D., committee member; Ozawa, Terutomo, committee member; Jianakoplos, Nancy, committee member (Colorado State University. Libraries, 2003)
The objective of this dissertation is to investigate evidence of economies of scale and scope, and to analyze the competitive conditions in the Jordanian banking market during the period 1990-2000. The analysis has been prompted by the monetary authority's claims that cost savings could be expected from the merger policy, which in turns promotes efficiency of banks in Jordan. Economies of scale and scope and the SCP relationship, a substantial part of the industrial organizations literature, have been widely examined in USA and European banking systems. The dissertation aims to rectify this imbalance in the literature by providing a detailed and in-depth analysis of scale and scope economies as well as structure performance relationship in the Jordanian banking market. The study estimates translog cost functions for the entire banking system, small banks, medium banks, large banks, domestic banks, and foreign banks. Then the estimated coefficients of the translog cost functions were utilized to compute the magnitudes of scale and scope economies. The study also estimates a full system of translog cost equations by using the technique of Zellner's iterative seemingly unrelated regression (SUR). Finally, the study analyzes the competitive conditions in the Jordanian banking market by estimating different specifications of profit equations. The main findings of the study on measure of overall economies of scale indicate that increasing returns to scale are observed in all classes of bank size as well as in foreign and domestic banks. The findings of the study suggest that the cost curves of the Jordanian banks were downward sloping in the years 1990-2000. Therefore, the findings of the study support the monetary authority's policy of encouraging banks to merge, particularly the small banks; since such policy will enable the banks to fully exploit economies of scale and will improve the banks' cost efficiency. This in turn will improve the efficiency of the banking market as a whole. The results of scope economies appear to be less clear-cut than the scale economy findings. The single translog cost function results show that the banking system experienced diseconomies of scope during 1990-2000. On the other hand, the results of the full system of translog cost equations suggest that cost complementarities do exist between loans and investments. These scale and scope economies results do not provide support for the existence of natural monopoly in the Jordanian banking system. The results obtained from investigating the competitive conditions in the Jordanian banking market show that the traditional structure-conduct-performance paradigm holds true in the Jordanian banking system, and this implies that the profit concentration relationship is positive. This result is robust with respect to model specifications and measurement of market concentration. The policy maker in Jordan has to make a judgment about the extent to which diminished competition, that may arise from merger policy, is offset by the benefits of lower costs, i.e. the amount of the expected savings in total costs should be compared to an estimate of the disadvantages, if any, of favoring larger banks.
Keywords: studies; estimates; dissertations and theses; reforms; efficiency; competition; hypotheses; decision making; copyright; literature reviews